Historical Changes in Histological Diagnosis of Lung Cancer - Mai Utada; Shuji Yonehara; Kotaro Ozasa (Journal of Epidemiology, 2019)
Background: Histological classification of lung cancer is essential for investigations of carcinogenesis and treatment selection. We examined the temporal changes of lung cancer histological subtypes. Methods: Lung cancer cases diagnosed in the Life Span Study cohort between 1958 and 1999 were collected from tumor registries (TR), mainly consisting of population-based cancer registries. A total of 1,025 cases were histologically reviewed according to the World Health Organization 2004 Classification by a panel of pathologists (PP). Sensitivity and specificity of diagnoses in TR were calculated, assuming that the diagnosis by PP was the gold standard. Results: Sensitivity and specificity were 0.91 and 0.92 for adenocarcinoma (AD), respectively, and 0.92 and 0.94, respectively, for squamous cell carcinoma (SQ). They were similar for AD and SQ throughout the observation period. For small cell carcinoma (SM), sensitivity was low until about 1980 (0.47 in 1958–1969, and 0.61 in 1970–1979) and then became higher thereafter (0.98 in 1980–1989, and 0.95 in 1990–1999), whereas specificity was high during the whole period (range 0.99 to 1.00). Among 45 cases that were not reported as SM in TR but diagnosed as SM by PP, 16 cases were recorded as undifferentiated carcinoma in TR. Conclusion: Diagnosis of AD and SQ of lung cancer were generally consistent between TR records and PP review, but SMs tended to be coded as other histological types until the 1970s.